A Comparative Study Between Contribution Percentages And The Effect Of Some Kinematical Variables Of Standing Vertical Jump Test Phases (Bending, Take-Off, Flight) With and Without Arm Swing On The Explosive Power Of Lower Limbs Muscles - Altay, Usama (Journal of Physical Education, 2007)
The aim of the research is to identify some Kinematical Variables of standing vertical jump test Phases (Bending, Take-Off, Flight) With and Without Arm Swing. also it aims at a comparing the contribution percentages and the effect of some kinematical variables of standing vertical jump test phases (bending, take-off, flight) with and without arm swing on the explosive power of lower limbs muscle. The researcher used the descriptive method, The subject were (25) student from physical education department/university of AL-Mustanseria in Baghdad. The researcher concluded that using arm swing to perform vertical jump is very important for measuring the height of the flight, So the best effect of the phases was the flight then the take-off followed by the bending phase. The percentage of contribution of kinematical variables of standing vertical jump test with arm swing were more compared to percentage of not using arm swing in explosive power of lower limps muscle. They recommended making similar studies by using Kinetical variables using force platform and time, as well as making similar studies on Kinemetical variables during flight phase.